Local Scour around Different-Shaped Bridge Piers - Siva K. Reddy; Sruthi T. Kalathil; Venu Chandra (Civil Engineering Journal, 2024)
Local scour around piers is the major cause of bridge failures, and its estimation is critical for safe design. The present study aims to identify a modified pier shape that can reduce local scour compared to a circular pier. In addition, M5 models are developed for maximum scour depth prediction and compared with the existing equations available in the literature. Thus, the effect of pier shape and alignment on local scour is experimentally investigated using three pier models with the same cross-sectional area placed in isolated and tandem arrangements under clear-water conditions. These are circular (M1) and two modified pier shapes (M2 and M3), where M2 is a combination of semi-circle and triangle oriented either way (M2a and M2b), and M3 is a further modification to M2a with a small protrusion on the semi-circular end. The results showed that the local scour depth for aligned (skew angle, α = 0°) M2a, M2b, and M3 piers is reduced by 23.5%, 50%, and 55%, respectively, compared to the M1 pier but not if α > 0°. In tandem arrangements, the least scour depths observed around M1 and M2a at X = 1.0D (X is clear-spacing between piers and D is pier diameter), and M3 and M1 at X = 1.75D placed as front and rear pier, respectively. It is observed that the developed M5 models are more accurate compared to the existing equations. Flow intensity (V/Vc) and αhave more influence on the scour depth prediction around tandem and isolated piers, respectively. Doi: 10.28991/CEJ-2024-010-06-019 Full Text: PDF